The van der Waals Interactions of n‐Alkanethiol‐Covered Surfaces: From Planar to Curved Surfaces. Issue 52 (30th November 2017) - Cometto, Fernando P.; Luo, Zhi; Zhao, Shun; Olmos‐Asar, Jimena A.; Mariscal, Marcelo M.; Ong, Quy; Kern, Klaus; Stellacci, Francesco; Lingenfelder, Magalí
Abstract: The van der Waals (vdW) interactions of n ‐alkanethiols (ATs) adsorbed on planar Au(111) and Au(100) surfaces and curved Au nanoparticles of different diameters are reported. By means of electrochemical measurements and molecular dynamic calculations, the increase in the average geometrical curvature of the surface influences the global interactions, that is, decreasing vdW interactions between neighboring molecules. Small NPs do not present the same electrochemical behavior as planar surfaces. The transition between nanoparticle to flat surface electrochemical response is estimated to occur at a circa 13–20 nm diameter range. Abstract : From planar to curved surfaces : The way that the geometrical curvature of the surface influences the global van der Waals interactions between thiol molecules is visualized by means of electrochemical measurements and molecular dynamic calculations.